Defamation law: are they aware? Do they know? / Hazlin Hasan … [et al.] - Hasan, Hazlin; Md Pauzi, Suria Fadhillah; Mustapha, Musramaini; Ghazali, Mohd Samsuri (2016)
By definition defamation is the act of injuring someone's character or reputation by expressing false statements that may lower that person's reputation in the eyes of the public. Regardless of race or religion, slander and gossips have been noted to cause destruction to the community and they are totally unacceptable to Islam and considered amongst the most destructive of major sins. With the extensive usage of social media among the youth and the many controversial issues debated in it, it is pertinent for the youths to be able to distinguish whether the statements they made are maliciously published. The researchers found it important to analyse the level of awareness and knowledge of these youth on defamation as these findings could be used to suggest programs that could equip them with necessary knowledge and assist them from unintentionally harming themselves out of ignorance. A total of 53 student leaders who attended a seminar on the awareness of defamation law were selected for this study. SPSS Version 23.0 software programme was used to analyse the frequencies, mean and standard deviation, maximum and minimum values. The study concluded that a majority of the student leaders was highly aware of the existence of defamation law but their level of knowledge on the law was found to be at an average level. The findings suggest that these young leaders still need to be educated further on the elements of the law in order to fill the gap of concerns on defamation, socially or religiously.